2007
DOI: 10.1177/1536867x0700700402
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Routines for Instrumental Variables/Generalized Method of Moments Estimation and Testing

Abstract: The Stata Journal and the contents of the supporting files (programs, datasets, and help files) are copyright c by StataCorp LP. The contents of the supporting files (programs, datasets, and help files) may be copied or reproduced by any means whatsoever, in whole or in part, as long as any copy or reproduction includes attribution to both (1) the author and (2) the Stata Journal. The articles appearing in the Stata Journal may be copied or reproduced as printed copies, in whole or in part, as long as any copy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
468
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(491 citation statements)
references
References 35 publications
(6 reference statements)
5
468
0
18
Order By: Relevance
“…Because of the recent publication of these legislations and the fact that only a few countries have imposed them, the results of this paper have strong economic and public policy implications, especially for the stakeholders, directors, and law makers (mainly market regulators and governments). Second, by using the test of endogeneity proposed by Baum et al (2007), we empirically analyze the existence of endogeneity in the relationship between gender diversity and firm performance. Third, to date, this is the third research work that studies the impact of the number of female corporate board memberships in the Spanish capital market, since most previous empirical evidences on this issue have been based on the US market.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the recent publication of these legislations and the fact that only a few countries have imposed them, the results of this paper have strong economic and public policy implications, especially for the stakeholders, directors, and law makers (mainly market regulators and governments). Second, by using the test of endogeneity proposed by Baum et al (2007), we empirically analyze the existence of endogeneity in the relationship between gender diversity and firm performance. Third, to date, this is the third research work that studies the impact of the number of female corporate board memberships in the Spanish capital market, since most previous empirical evidences on this issue have been based on the US market.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of dividing our statistical method into two steps is to address the concern of potential endogeneity and causality associated with the relations between the number of women in the boardroom and financial performance. In addition, to assume from a theoretical view that the relationship between gender diversity and financial performance is endogenously determined, we empirically test this by using the GMM distance test of endogeneity proposed by Baum et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of the instrumental variables used in the past [30,46,47] were found to be unsatisfactory. 6 We applied the IVREG2 routine in Stata/SE 11.1 to our cost equation [51,52] to test the validity of our instruments and found that our model did not pass overidentification and weak identification tests.…”
Section: Measure Of Hospital Inefficiencymentioning
confidence: 99%
“…(1)] was unnecessary, we note that in our PM 2.5 regression model moving average processes eliminate a potential repetitive seasonal component in the dependent variable (Maddala and Kim 1998). In the IV PM 2.5 regression equation, we use a HAC weighting matrix to correct for autocorrelation, the main source of which is seasonality (Baum et al 2007). 15 A 4-month interval was necessary in order to obtain a large enough subsample for econometric estimation.…”
Section: Pm 25 and Gas-price Regression Modelsmentioning
confidence: 99%